Investigation of Problem-Based Learning (PBL) on Physics Education Technology (PhET) Simulation in Improving Student Learning Outcomes in Acid-Base Material - Aceng Haetami; Nina Zulvita; Dahlan; Maysara; M. Alim Marhadi; Tri Santoso (Jurnal Penelitian Pendidikan IPA, 2023)
This study aimed to ascertain how well the problem-based learning model and physics education technology (PhET) simulation improved student learning outcomes in acid-base materials. The research method used was a quasi-experiment with a non-equivalent control group design. Data collection techniques were used in this study by providing test instruments in the form of multiple-choice questions, pretests and posttests, and observation sheets of teacher and student activities. The findings revealed that students taught using the PBL model with PhET simulation achieved an average learning outcome score of 79.29, while those taught using the PBL model alone obtained an average score of 73.97. The calculated average N-gain of 0.70 (categorized as medium) indicates that the PBL model with PhET simulation significantly contributed to enhancing student learning outcomes. This study demonstrates that integrating the PBL model with PhET simulation is an effective approach for improving student learning outcomes in the context of acid-base materials. The results highlight the importance of experiential, inquiry-based approaches combined with technology in enhancing student engagement and understanding. Further research could explore the long-term effects of implementing this instructional approach and investigate its impact on broader aspects of student learning in science education.